Efficacy and safety of cold snare polypectomy for sessile serrated polyps ≥ 10 mm: A systematic review and meta-analysis. Issue 11 (November 2022) - Li, De-feng; Van Overbeke, Lode; Ohata, Ken; Wang, Li-sheng; Yao, Jun
Abstract: Background: Cold snare polypectomy (CSP) is a promising technique for the removal of sessile serrated polyps (SSPs) ≥ 10 mm. However, the efficacy and safety of this technique remain undetermined. Aims: We aimed to comprehensively evaluate the efficacy and safety of CSP for SSPs ≥ 10 mm. Methods: PubMed, EMBASE, Web of Science and Cochrane Library were searched up to January 2021. Results: A total of 10 studies consisting of 1727 SSPs (range, 10–40 mm) from 1021 patients were included. The overall rates of technical success, adverse events (AEs) and residual SSPs were 100%, 0.7% and 2.9%, respectively. Subgroup analysis showed that the rates of technical success and AEs were comparable between CSP and cold endoscopic mucosal resection (EMR) (99.9% vs. 100% and 1.3% vs. 0.5%, respectively), between the proximal and distal colon (100% vs. 99.9% and 0.3% vs. 0, respectively), and between polyps of 10–19 mm and ≥20 mm (99.8% vs. 100% and 0.9% vs. 0, respectively). However, subgroup analysis showed that the rate of residual SSPs was slightly lower in CSP compared with cold EMR (1.3% vs. 3.9%), as well as in polyps of 10–19 mm compared with those ≥20 mm (3.1% vs. 4.7%). Conclusion: CSP was an effective and safe technique for removing SSPs ≥ 10 mm.